Implementation of Telegram Chatbot as Information Service of Madani Hospital Pekanbaru - hariansyah, Aldi; Haerani, Elin; Novriyanto, Novriyanto; Affandes, Muhammad (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Udayana, 2023)
very institution or organization aims to create a positive image through information services. In Indonesia, many hospitals provide information through telephone or official websites. However, Madani Hospital in Pekanbaru requires improvement. This research developed a registration chatbot on Telegram, making it easier for patients to make doctor appointments, view schedules, and access important information. Telegram was chosen for being lightweight, fast, and popular. The research involved literature surveys, problem identification, literature review, and data collection. The results were used to design the chatbot flow. The system was developed using Sommerville's Waterfall method, covering requirement definition, design, implementation, testing, integration, operation, and improvement. User Acceptability Testing is a key stage in implementation. User Acceptability Testing questionnaires were distributed to 20 prospective patients with various questions. The chatbot implementation used the Python API for Telegram and a MySQL database, with Black Box testing covering patient access, registration, functions, admin authentication, create update read delete admin, and error handling. The results of User Acceptability Testing showed an accuracy achievement of 77.8%, which means it is Very Good.